Spermatic Vein Tumor Thrombus In Renal Cell Carcinoma - Nicola J. Mabjeesh; Yuval Bar-Yosef; Letizia Schreiber-Bramante; Issac Kaver; Haim Matzkin (The Scientific World Journal)
Renal cell carcinoma has the tendency to form venous thrombi. This may involve the renal veins or the inferior vena cava and may extend cephalad/antegrade into the right atrium. We report a patient with renal cell carcinoma who had an intracaval tumor thrombus that had extended into the right spermatic vein. We believe this to be the first description in English literature of a histologically proven renal cell carcinoma thrombus in the spermatic vein.